Molecular modelling of betalactamic antibiotic - Elso Manuel Cruz Cruz; Grettel Díaz Ramón (Medisur)
Background: The antibacterial properties of a compound are the result of its molecular structure. To establish the structural and electronic characteristics makes possible to understand the mechanisms of its action and becomes paramount for the rational design new drugs. Objective: To model some of the molecular properties of betalactamic antibiotics and inhibitors of the betalactamases and to relate them with their pharmacological actions. Method: The molecular structures were optimized with PM3• semiempiric calculus. The structure of the betalactamic ring in the different compounds was compared. The molecular properties were calculated according to the Density Functional Theory at a B3LYP/6-31G(d) level. The density of the atomic charges and the frontier orbitals were analyzed. Results There are variations in the calculated properties that make possible to define two groups of compounds: one for the monobactams and the inhibitors of the betalactamases, with less planarity in the ring and less reactivity and another one with the penicillins, cephalosporins and carbapenems, planer, more structurally stable and reactive. Conclusions: The modelled molecular properties of the betalactamic antibiotics and inhibitors of the betalactamases show agreement with its pharmacological action.